2011
DOI: 10.1002/jssc.201100189
|View full text |Cite
|
Sign up to set email alerts
|

Applications of monolithic columns in liquid chromatography‐based clinical chemistry assays

Abstract: Monolithic columns have slowly been applied to HPLC methods for clinical chemistry testing in the last 10 years. The application areas include therapeutic drug monitoring, drugs of abuse, vitamins, porphyrins, and steroids. In comparison with conventional particulate columns, the monolithic columns may offer shorter chromatography time, more robustness, and better resolution for certain analytes. The potential drawback of large mobile phase consumption may be improved with smaller id columns, which are current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 63 publications
(145 reference statements)
0
7
0
Order By: Relevance
“…The polymer has the potential to be used as SPE packing for the simultaneous enrichment of steroid hormones and other hydrophobic compounds at a trace level. A monolithic HPLC column may take shorter chromatography time, but provide more robustness and a better resolution for certain analytes in comparison with conventional particulate columns . These observations emphasize the need for further studies focusing on the application of custom‐made SPE in a monolithic column.…”
Section: Discussionmentioning
confidence: 99%
“…The polymer has the potential to be used as SPE packing for the simultaneous enrichment of steroid hormones and other hydrophobic compounds at a trace level. A monolithic HPLC column may take shorter chromatography time, but provide more robustness and a better resolution for certain analytes in comparison with conventional particulate columns . These observations emphasize the need for further studies focusing on the application of custom‐made SPE in a monolithic column.…”
Section: Discussionmentioning
confidence: 99%
“…This feature enables the use of MCs in low-pressure flow systems, such as in SIC systems. Other advantages are fast mass transfer and fast separations without sacrificing separation efficiency (Bunch and Wang, 2011;Gomez and Callao, 2007;Guiochon, 2007;Jiang et al, 2011;Mistry and Grinberg, 2005;Rieux et al, 2005;Unger et al, 2008). The developments in retentive phases, formats, and dimensions of MCs have resulting in the adoption of such chromatographic modes as reversed-phase chromatography, ion-exchange chromatography, hydrophilic interaction chromatography, size-exclusion chromatography, molecular imprints, and affinity chromatography.…”
Section: Introductionmentioning
confidence: 97%
“…The developments in retentive phases, formats, and dimensions of MCs have resulting in the adoption of such chromatographic modes as reversed-phase chromatography, ion-exchange chromatography, hydrophilic interaction chromatography, size-exclusion chromatography, molecular imprints, and affinity chromatography. Therefore, the applications of MCs have been extended to various analytical fields including pharmaceutical, food, environmental, and clinical (Bunch and Wang, 2011;Fernández et al, 2012;Gomez and Callao, 2007;Guiochon, 2007;Jiang et al, 2011;Mistry and Grinberg, 2005;Rieux et al, 2005;Unger et al, 2008). A review article on the use of MCs in SIC has been recently published (Fernández et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…Many published studies showed the applicability potential of silica-based monolithic columns in investigations of various samples, including plants [ 17 , 18 , 19 , 20 ], food [ 21 , 22 , 23 ], dietary supplements [ 24 ], and drugs [ 25 , 26 , 27 ]. So far, numerous review papers described the analytical use of monolithic columns [ 1 , 4 , 5 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Namera et al showed applications of different types of commercially available silica-based monolithic columns in the analysis of active compounds in biological materials.…”
Section: Introductionmentioning
confidence: 99%